2010
DOI: 10.5012/bkcs.2010.31.9.2509
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Trp-rich Model Antimicrobial Peptoid with Increased Protease Stability

Abstract: In order to increase protease stability of a novel Trp-rich model antimicrobial peptide, K6L2W3 (KLWKKWKKWLK-NH2) and investigate the effect of L-amino acid to peptoid residue conversion on biological functions, we synthesized its antimicrobial peptoid, k6l2w3. Peptoid k6l2w3 had similar bacterial selectivity compared to peptide K6L2W3. The bactericidal rate of k6l2w3 was somewhat slower than that of K6L2W3. Peptoid k6l2w3 exhibited very little dye leakage from bacterial outer-membrane mimicking PE/PG liposome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…The MICs required to completely inhibit the growth of bacteria were within the range of 2 to 64 g/ml and revealed high to moderate antimicrobial peptoid activity throughout the library compared to that of structurally similar antimicrobial peptides, such as Bac8c indolicidin and omiganan (Table 1.) (23). This is in agreement with other reported MICs of peptides and peptidomimetics that contain lysine and tryptophan side chains (3,24,25). Peptoids 1, 7, and 15 are mimics of GN-2, GN-4, and GN-6 peptides, respectively (22), and the broad-spectrum antimicrobial activities were not improved upon making these structural changes (Table 1; see also Fig.…”
Section: Resultssupporting
confidence: 79%
“…The MICs required to completely inhibit the growth of bacteria were within the range of 2 to 64 g/ml and revealed high to moderate antimicrobial peptoid activity throughout the library compared to that of structurally similar antimicrobial peptides, such as Bac8c indolicidin and omiganan (Table 1.) (23). This is in agreement with other reported MICs of peptides and peptidomimetics that contain lysine and tryptophan side chains (3,24,25). Peptoids 1, 7, and 15 are mimics of GN-2, GN-4, and GN-6 peptides, respectively (22), and the broad-spectrum antimicrobial activities were not improved upon making these structural changes (Table 1; see also Fig.…”
Section: Resultssupporting
confidence: 79%
“…Both peptoids have relatively short sequences (9 residues, Fig. 1 ) and exhibit MIC ( ≤ 22.2 μM) values that are comparable to that of the antimicrobial peptide indolicidin ( Table 1 ) and are within the range of other antimicrobial peptoids reported in the literature 8 17 .…”
Section: Resultssupporting
confidence: 57%
“…Bang et al reported the conversion of a Trp-rich peptide, H-KLWKKWKKWLK-NH 2 , into the corresponding protease-stable peptoid without loss of potency or increase in hemolytic properties [ 181 ]. Interestingly, the killing kinetics of the Trp-rich peptide and the peptoid analog were compared at 8 μM (1 or 2 × MIC) against E. coli and S. aureus , and it was found that the bactericidal rate of the peptoid (60 min) was slower than that of the peptide (30 min), indicating different killing mechanisms.…”
Section: Peptidomimeticsmentioning
confidence: 99%